Topical Application of Apricot Kernel Extract Improves Dry Eye Symptoms in a Unilateral Exorbital Lacrimal Gland Excision Mouse - Chan-Sik Kim (Nutrients, 2016)
The purpose of this study was to investigate the therapeutic effects of topical application of apricot kernel extract (AKE) in a unilateral exorbital lacrimal gland excision mouse model of experimental dry eye. Dry eye was induced by surgical removal of the lacrimal gland. Eye drops containing 0.5 or 1 mg/mL AKE were administered twice a day from day 3 to day 7 after surgery. Tear fluid volume and corneal irregularity scores were determined. In addition, we examined the immunohistochemical expression level of Muc4. The topical administration of AKE dose-dependently improved all clinical dry eye symptoms by promoting the secretion of tear fluid and mucin. Thus, the results of this study indicate that AKE may be an efficacious topical agent for treating dry eye disease.